Pharmacological potential of Holothuria (Mertensiothuria) leucospilota (Brandt, 1835): antibacterial activity against methicillin-resistant Staphylococcus aureus and metabolite profile - Ceesay, Abdoulie; Nazarudin, Muhammad Farhan; Mohamed Alipiah, Norfarrah; Md Yasin, Ina Salwany; Azmai Amal, Mohammad Noor; Mohd Sayuti, Mohamad Azzam; Ismail, Intan Safinar; Aliyu-Paiko, Mohammed (Springer Science and Business Media Deutschland, 2025)
Throughout history, the sea cucumber species Holothuria leucospilota has played a role in traditional medicine, serving as a therapeutic agent for various ailments. This study delves into the antibacterial efficacy of H. leucospilota extracts against clonally diverse Sequenced Type (ST) methicillin-resistant Staphylococcus aureus (MRSA) strains prevalent in Malaysia, as well as methicillin-sensitive Staphylococcus aureus (MSSA). Initial susceptibility screening involved disc diffusion and broth microdilution methods. Assessment of the crude extracts’ bacteriostatic and bactericidal properties, employing conventional measures of bacterial population reduction and a time-kill assay, revealed intriguing results. Resistance to body wall, cuvierian tubules, and visceral extracts was observed in Gram-positive MRSA and ST MSSA clones (SCCmec Sequenced Type) and Gram-negative MRSA and ST MSSA clones (ExPEC ESBL-producing). Minimum inhibitory concentration (MIC) ranged from 8 to 128 mg/mL, and minimum bactericidal concentration (MBC) ranged from 32 to 128 mg/mL, consistent with antibacterial assays involving plants. Time-kill assay findings demonstrated bactericidal activity against Gram-positive MRSA and MSSA bacteria after 12 h and bacteriostatic activity against Gram-negative E. coli bacteria after 8 h. Additionally, the extract displayed bacteriostatic activity against both groups of bacteria after 6 h. Furthermore, Gas Chromatography - Mass Spectrometry profiling identifies a rich array of metabolites in different extracts, suggest that H. leucospilota harbors chemical compounds with potential applications in ointments, dietary supplements, pharmaceuticals, and antibacterial therapies. The study underscores the pharmacological promise of this sea cucumber species in contributing to diverse medical and therapeutic avenues.